Ethnonational Conflict: A Study of the Anglophone Crisis in Cameroon - Akintola, Mercy Oluwanisola (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
When the Cold War ended in the late 1980s, a multiplicity of intrastate conflicts occurred, which exposed many countries to conflicts that had their roots in a range of concerns, including power sharing, ethnicity, resource control, and distribution. The majority of these conflicts are located in Africa. In the Anglophone regions of Cameroon, protests around sectoral demands have turned into a political crisis since October 2016. The Anglophone Problem has returned as a result of this crisis, which has also revealed the shortcomings of Cameroon's centralized, elite-coopted governance system. Using a few conflict theories, this thesis seeks to analyze the ongoing Anglophone struggle. I use theories like PSC, physiccultural conflict theory, and structural conflict theory to support my contention that the Anglophone dispute is a long-running social and ethnic struggle rather than an isolated incident. In that the bulk of the characteristics accurately reflect the emergence and progression of this specific situation, Azar's framework of "Protracted Social Conflict" serves as a valid explanation of the conflict in Cameroon. My analysis results demonstrate that Azar's Protracted Social Conflict framework is an appropriate way to describe the conflict in Anglophone protracted social conflict since majority of the criteria accurately define the conflict and its development. Azar's framework of "Protracted Social Conflict" is a legitimate description of the conflict in that the majority of factors are appropriately mirrored in the emergence and evolution of this particular. Structural institutional discrimination, and a crisis in group identification are the primary causes of the conflict. I argue that the Anglophone conflict is a result of the difference in colonial leadership of the past of both Anglophone and Francophone Cameroon and the weak negotiations of the reunification terms. International and regional actors this includes state and non-states actors find it hard to intervene in the conflict because of their relation with the Cameroon. Though there has been no fruitful mediation process in the Cameroon conflict, I argue that factors like economic interest is the reason why external actors have not intervened yet

ÖZ: 1980'lerin sonlarında Soğuk Savaş sona erdiğinde, birçok ülkeyi güç paylaşımı, etnik köken, kaynak kontrolü ve dağıtım dahil olmak üzere bir dizi endişeye dayanan çatışmalara maruz bırakan çok sayıda devlet içi çatışma meydana gelmiştir. Bu çatışmaların çoğu Afrika'da bulunmaktadır. Kamerun'un Anglofon bölgelerinde Ekim 2016'dan bu yana sektörel taleplere yönelik protestolar siyasi bir krize dönüşmüştür. Bu kriz sonucunda Anglofon Sorunu geri dönmüş ve Kamerun'un merkezi, elitlerin oluşturduğu yönetişim sisteminin eksikliklerini de ortaya çıkarmıştır. Bu tez, farklı çatışma teorilerini kullanarak, süregiden Anglofon mücadelesini analiz etmeyi amaçlamaktadır. Anglofon anlaşmazlığının münferit bir olaydan ziyade uzun süredir devam eden sosyal ve etnik bir mücadele olduğu yönündeki iddiamı desteklemek için PSC, fizik-kültürel çatışma teorisi ve yapısal çatışma teorisi gibi teorileri kullanılmıştır. Azar'ın "Uzun Süreli Sosyal Çatışma" çerçevesi, özelliklerin büyük kısmının bu özel durumun ortaya çıkışını ve ilerlemesini doğru bir şekilde yansıtması nedeniyle Kamerun'daki çatışmanın geçerli bir açıklaması olarak hizmet etmektedir. Analiz sonuçlarım, Azar'ın Uzun Süreli Sosyal Çatışma çerçevesinin Anglofon uzun süreli sosyal çatışmadaki çatışmayı tanımlamanın uygun bir yolu olduğunu göstermektedir. Bunun nedeni, kriterlerin çoğu, çatışmayı ve gelişimini doğru bir şekilde tanımlıyor. Azar'ın "Uzun Süreli Sosyal Çatışma" çerçevesi, faktörlerin çoğunun bu özel durumun ortaya çıkışında ve evriminde uygun şekilde yansıtıldığı çatışmanın meşru bir tanımıdır. Yapısal kurumsal ayrımcılık ve grup kimliğindeki bir kriz, çatışmanın başlıca nedenleridir. Tez, Anglofon çatışmasının, hem Anglofon hem de Frankofon Kamerun'un geçmişteki sömürge liderliğindeki farklılığın ve yeniden birleşme koşullarının zayıf müzakerelerinin bir sonucu olduğunu savunmaktadır. Buna devlet ve devlet dışı aktörler de dahil olmak üzere uluslararası ve bölgesel aktörler, Kamerun ile olan ilişkileri nedeniyle çatışmaya müdahale etmekte zorlanmaktadır. , Bu çalışma, Kamerun ihtilafında verimli bir arabuluculuk süreci olmamasına rağmen, dış aktörlerin henüz müdahale etmemesinin nedeninin ekonomik çıkar gibi faktörlerin olduğunu da savunmaktadır.
Master of Arts in Diplomacy and Conflict Management. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2022. Supervisor: Assist. Prof. Dr. Gülay Umaner Duba.
Keywords: Thesis Tez; Political Science and International Relations Department; Diplomacy and Conflict Management; Politics and government--Cameroon; Social conditions--Cameroon; Ethnic Conflict; Protracted Social Conflict; Anglophone Conflict; Cameroon